Characterization of a Novel Class of Polyphenolic Inhibitors of Plasminogen Activator Inhibitor-1 - Cale, Jacqueline M. (American Society for Biochemistry and Molecular Biology, 2010)
Plasminogen activator inhibitor type 1, (PAI-1) the primary inhibitor of the tissue-type (tPA) and urokinase-type (uPA) plasminogen activators, has been implicated in a wide range of pathological processes, making it an attractive target for pharmacologic inhibition. Currently available small-molecule inhibitors of PAI-1 bind with relatively low affinity and do not inactivate PAI-1 in the presence of its cofactor, vitronectin. To search for novel PAI-1 inhibitors with improved potencies and new mechanisms of action, we screened a library selected to provide a range of biological activities and structural diversity. Five potential PAI-1 inhibitors were identified, and all were polyphenolic compounds including two related, naturally occurring plant polyphenols that were structurally similar to compounds previously shown to provide cardiovascular benefit in vivo. Unique second generation compounds were synthesized and characterized, and several showed IC(50) values for PAI-1 between 10 and 200 nm. This represents an enhanced potency of 10–1000-fold over previously reported PAI-1 inactivators. Inhibition of PAI-1 by these compounds was reversible, and their primary mechanism of action was to block the initial association of PAI-1 with a protease. Consistent with this mechanism and in contrast to previously described PAI-1 inactivators, these compounds inactivate PAI-1 in the presence of vitronectin. Two of the compounds showed efficacy in ex vivo plasma and one blocked PAI-1 activity in vivo in mice. These data describe a novel family of high affinity PAI-1-inactivating compounds with improved characteristics and in vivo efficacy, and suggest that the known cardiovascular benefits of dietary polyphenols may derive in part from their inactivation of PAI-1.